PENGARUH PUPUK ORGANIK LIMBAH CAIR KELAPA SAWIT (LCKS) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KANGKUNG DARAT Ipomea reptans poir - Widya Lestari (JURNAL AGROPLASMA, 2019)
The design used randomized block design (RAK) factorial one with five treatments; P0: 0 ml/ liter without liquid organic fertilizer (control), P1: 5 ml / liter, P2: 10 ml / liter, P3: 15 ml / liter, P4: 20 ml / liter, followed by Duncan test. Parameters measured were plant height (cm), number of leaves (leaf), plant fresh weight (g), stem diameter (cm). of the research results obtained the following conclusions (1) Organic fertilizer liquid waste palm oil significantly affected plant height Kale 2 and 4 MST MST. (2) Organic fertilizer liquid waste palm significant effect on stem diameter. kale (3) Organic fertilizer liquid waste palm oil significantly affect the number of leaves of kale. (4) Organic fertilizer liquid waste palm real impact on plant fresh weight of spinach. Keywords: organic fertilizer liquid waste palm oil, growth, production amaranth